Resolving execution of judgment in Indonesia investment fraud case to ensure asset recovery for victims = Resolución de la ejecución de sentencia en un caso de fraude de inversiones en Indonesia para garantizar la recuperación de los activos de las víctimas = Resolução da execução da sentença no caso de fraude de investimento na Indonésia para garantir a recuperação de ativos para as vítimas - Prayitno, Kuat Puji (Revista Criminalidad, 2024)
In response to investment fraud, the criminal justice system should place the victim at the centre, considering their financial loss. Indonesia has responded by establishing asset recovery for victims; however, there are signs of stagnation in its execution. This study aims to explain the causes and solutions to such stagnation so that victims can benefit from the justice system. This study uses a case study and statutory approach to analyse the operation of execution provisions in asset recovery. A case in the city of Cirebon (West Java Province) was selected because the execution has not been completed despite having been initiated since 2017 to prevent similar failures, as Indonesian courts have now tended to favour asset recovery. Primary data were obtained from interviews with officers directly involved in the execution of the case, supplemented by secondary data obtained through regulatory analysis and a literature study. This article discloses the serious problems in asset liquidation faced by executing agencies, as perpetrators have already completed their prison terms, even though victims have yet to receive their entitlements. Prolonged stagnation has led to the perception that access to asset recovery is non-executable. This study offers a solution towards synchronising regulations and empowering the resources of the criminal justice system more optimally.